THE IMPACT OF ENTREPRENEURIAL KNOWLEDGE AND SOCIAL MEDIA ON BUSINESS SUCCESS: THE MODERATING ROLE OF FAMILY SUPPORT IN WOMEN’S FASHION MSMEs in CENTRAL JAKARTA - Putera, Samahita; Ie, Mei (Graduate Program of Universitas Tarumanagara, 2025)
The importance of entrepreneurial knowledge and social media in increasing the success of women's fashion MSMEs in Central Jakarta, especially amidst increasingly tight business competition. This study aims to analyze the influence of these two factors on business success by considering family support as a moderating factor. Entrepreneurial knowledge helps business actors in recognizing opportunities, managing risks, and adapting in a dynamic and competitive market. Meanwhile, social media acts as an effective marketing tool to reach consumers at a relatively low cost. Family support is believed to provide additional stability and motivation for MSME owners. This study uses a descriptive quantitative method with a Partial Least Square-Structural Equation Modeling (PLS-SEM) approach and involves 106 respondents of women's fashion MSMEs in Central Jakarta. The results of the study indicate that entrepreneurial knowledge has a positive and significant influence on business success. However, the influence of social media on business success is positive but not significant. In addition, family support has a positive and significant influence on business success. As a moderating variable, family support is not significant in moderating the influence of entrepreneurial knowledge and social media on business success. This study suggests that MSMEs should focus more on improving their understanding of entrepreneurship and maximizing the use of social media effectively, while further research can expand the scope of business sectors and variables studied for more comprehensive results.